Introduction: Indigenous futurities in education - Marnee Shay; Maria Raciti; Bronwyn Fredericks; Tracey Bunda (The Australian Journal of Indigenous Education)
Indigenous education is multidimensional and multifaceted. When the term “Indigenous education” is used, it could reference schooling practices, including embedding Indigenous knowledge and perspectives in the curriculum; connecting with Indigenous communities; supporting Indigenous students; employing Indigenous staff; and more (Shay et al., 2023). The enactment or inaction of these activities is underpinned by ideological dissonance between Western theories and ideals and Indigenous knowledge paradigms and values.